Sasak Language in Rituals and Traditions: An Anthropological Analysis of Communication in the Lombok Community - Nasri, Ulyan; Indinabila, Yunita; Rasyidi, Abdul Haris (Sabda: Jurnal Kajian Kebudayaan, 2024)
The Sasak language plays a vital role in the rituals and traditions of the Lombok community. This study aims to analyze the use of the Sasak language in the context of anthropological communication, particularly in ritual and traditional activities in Lombok. This research uses a qualitative approach with ethnographic methods. Data collection techniques include participant observation, in-depth interviews, and documentation. Data analysis was conducted using thematic analysis techniques to identify patterns and meanings in the use of the Sasak language in various rituals and traditions. The research results show that the Sasak language is widely used in various religious rituals, traditional ceremonies, and celebrations. The use of this language serves not only as a communication tool but also as a symbol of cultural identity and social cohesion. In conclusion, the Sasak language plays a crucial role in preserving and transmitting cultural values and strengthening social cohesion within the Lombok community. The implications of this research highlight the importance of preserving the Sasak language in the context of modernization and globalization to ensure the continuity of the traditions and cultural identity of the Sasak people.